Application of the tolerance averaging method to analysis of dynamical stability of thin periodic plates. - Jędrysiak, Jarosław (Polskie Towarzystwo Mechaniki Teoretycznej i Stosowanej, 2004)
Some problems of a dynamical stability of thin periodic plates are considered. As a tool to derive the governing equations of an averaged non-asymptotic plate model the tolerance averaging is applied, proposed for periodic composites and structures by Woźniak and Wierzbicki (2000). This method applied to the known Kirchoff-type plate equation leads to averaged models taking into account the effect of the period lengths on the overall plate behaviour (Jędrysiak, 2001). Here, a non-asymptotic model describing the problems of a dynamical stability of periodic plates is formulated. Moreover, it is shown that the effect of the period lengths plays a crucial role in some special cases of dynamical stability of such plates, i.e. for higher oscillation frequencies of compressive forces in the plate midplane.

W pracy rozpatrzono pewne zagadnienia dotyczące stateczności dynamicznej cienkich płyt o periodycznej budowie. Przy wyprowadzeniu równań uśrednionego modelu nieasymptotycznego wykorzystano tolerancyjne uśrednianie, zaproponowane przez Woźniaka i Wierzbickiego (2000) do modelowania kompozytów i struktur periodycznych. Zastosowanie tej metody do znanego równania teorii płyt Kirchhoffa prowadzi do modeli uśrednionych, w których uwzględniony jest wpływ długości okresów periodyczności na pracę płyty (Jędrysiak, 2001). W pracy sformułowano nieasymptotyczny model opisujący zagadnienia stateczności dynamicznej płyt periodycznych. Pokazano również, że wpływ długości okresów periodyczności odgrywa znaczącą rolę w pewnych szczególnych przypadkach stateczności dynamicznej takich płyt, np. dla wysokich częstości oscylacji sił ściskających, przyłożonych w płaszczyźnie środkowej płyty.
Zastosowanie metody tolerancyjnego uśredniania do analizy stateczności dynamicznej cienkich płyt periodycznych.
Keywords: thin periodic plate; dynamical stability; the length-scale effect; statyczność dynamiczna; cienkie periodyczne płyty; model nieasymptotyczny; tolerancyjne uśrednianie; struktury periodyczne